Power converters control for photovoltaic water pumping system - Tangerino, Bruno Henrique Boschetti (2019)
This work proposes solutions to challenges encountered in photovoltaic water pumping systems, such as the issue in the number of photovoltaic modules in low power systems, the maximum power point tracking and its implementation, as well as the pump control system. The maximum power point tracking is achieved via the addition of a step-up converter controlled by a proportional-integral controller. The system load is comprised by an induction motor, controlled by an open-loop scalar strategy. Simulations and real platform tests with solar radiance variation and variable number of photovoltaic modules were performed, validating the operation of the proposed solutions.